Correlating sugarcane productivity in Halfa, Sennar and Kenana sugar cane schemes to time course and annual rainfall - Mohamed, Habiballa (Gezira Journal of Agricultural Science, 2015)
Sugarcane ( Saccharum officinarum L . ) has a long growing season, normally 15 to 16 months and is grown between latitudes 35 ◦ north and south of the equator (Abdel Wahab, 2009). There is shortage of information about sugarcane in the Sudan (Abbas and El-Hag, 2013). According to Abdel Wahab(2009), knowledge about water relations is fundamental to improved crop management in these regions. In fact, all sugar growing schemes in the Sudan were established in the arid and the semi-arid zones. In these zones, irrigation is costly (Mohamed, 2013). An important aspect of sugar cane management is the correct irrigation in terms of interval and amount. The objective of this study was to highlight some aspects of sugarcane productivity in relation to the time course and annual rainfall in three of the sugar schemes in the Sudan; Halfa, Sennar and Kenana, with the purpose of further improvement in their productivities.                                                                                                                                                                                                                                                                                                                                                                                                                Halfa lies in an arid climate, with the coordinates 15.32 ◦ north and 35.6 ◦ east. The mean annual rainfall for the period 1975-2004 is about 228.3mm/annum, with a standard deviation of 117.5 and a standard error of 21.4. The maximum annual rainfall was 543mm and the minimum was 33.4mm. Sennar lies in a semi-arid climate with coordinates13.55 ◦ north and 33.62 ◦ . The mean annual rainfall in Sennar Sugar Scheme for the period 1979-2014 is 365.3mm, the standard deviation is 102.9, and the standard error is 16.4mm. The maximum rainfall during the period was 580.7mm and the minimum was 174.7mm. Kenana lies in a semi-arid climate at latitude 13.10 ◦ north and longitude 32.40 ◦ east.The mean annual rainfall in Kenana sugar scheme for the period 1975-2005 is 371.1mm/annum with a standard deviation of 119.7 and a standard error of 23.0. Maximum annual rainfall was 641.9 mm and the minimum was 89.1 mm. شملت هذه الدراسة ثلاثة من مشاريع السكر بالسودان وهى حلفا وسنار وكنانة وهدفت الى القاء الضوء على العلاقة بين انتاجية الفدان من القصب والسكر من جهة، ومعدلات الامطار السنوية  تقدم الزمن من الجهة الأخرى. تم الحصول على معدلات الامطار للفترات المعنية للمشاريع  الثلاثة وكذلك الحصول على معلومات الانتاجية من المشايع المعنية. استخدم برنامج التحليل الإحصائي (Excel) لإيجاد الارتباط بين الانتاجية والعوامل الاخرى. أوضحت الدراسة أن انتاجية الفدان من القصب انخفضت مع ازدياد المعدل السنوي للأمطار في كل من حلفا وسنار    وعلى العكس ازدادت في كنانة. وأن انتاجية الفدان من القصب ازدادت مع الزمن وباستمرار في كل من سنار وكنانة و كانت الزيادة طفيفة في حلفا. وأن انتاجية الفدان من السكر ازدادت مع الزمن و باستمرار في كل من سنار وكنانة و كانت الزيادة طفيفة في حلفا. وأن نسبة  انتاجية الفدان من السكر للقصب ظلت ثابتة مع الزمن وهى حوالى 0.09 في كل من حلفا وكنانة وحوالى 0.1 في سنار. ويمكن اجراء المزيد من الدراسة للاستفادة من الامطار في كل من حلفا وسنار كما يمكن الافادة من تجربة سنار فيما يتعلق بنسبة السكر الاعلى.